The benefit of minocycline on negative symptoms of schizophrenia in patients with recent-onset psychosis (BeneMin): a randomised, double-blind, placebo-controlled trial. (November 2018) - Deakin, Bill; Suckling, John; Barnes, Thomas R E; Byrne, Kelly; Chaudhry, Imran B; Dazzan, Paola; Drake, Richard J; Giordano, Annalisa; Husain, Nusrat; Jones, Peter B; Joyce, Eileen; Knox, Emma; et al.
Summary: Background: The antibiotic minocycline has neuroprotective and anti-inflammatory properties that could prevent or reverse progressive neuropathic changes implicated in recent-onset schizophrenia. In the BeneMin study, we aimed to replicate the benefit of minocycline on negative symptoms reported in previous pilot studies, and to understand the mechanisms involved. Methods: In this randomised, double-blind, placebo-controlled trial, we recruited people with a schizophrenia-spectrum disorder that had begun within the past 5 years with continuing positive symptoms from 12 National Health Service (NHS) trusts. Participants were randomly assigned according to an automated permuted blocks algorithm, stratified by pharmacy, to receive minocycline (200 mg per day for 2 weeks, then 300 mg per day for the remainder of the 12-month study period) or matching placebo, which were added to their continuing treatment. The primary clinical outcome was the negative symptom subscale score of the Positive and Negative Syndrome Scales (PANSS) across follow-ups at months 2, 6, 9, and 12. The primary biomarker outcomes were medial prefrontal grey-matter volume, dorsolateral prefrontal cortex activation during a working memory task, and plasma concentration of interleukin 6. This study is registered as an International Standard Randomised Controlled Trial, number ISRCTN49141214, and the EU Clinical Trials register (EudraCT) number is 2010-022463-35I. Findings: Between April 16, 2013, and April 30, 2015, we recruited 207 people and randomly assigned them to receive minocycline (n=104) or placebo (n=103). Compared with placebo, the addition of minocycline had no effect on ratings of negative symptoms (treatment effect difference −0·19, 95% CI −1·23 to 0·85; p=0·73). The primary biomarker outcomes did not change over time and were not affected by minocycline. The groups did not differ in the rate of serious adverse events (n=11 in placebo group and n=18 in the minocycline group), which were mostly due to admissions for worsening psychiatric state (n=10 in the placebo group and n=15 in the minocycline group). The most common adverse events were gastrointestinal (n=12 in the placebo group, n=19 in the minocycline group), psychiatric (n=16 in placebo group, n=8 in minocycline group), nervous system (n=8 in the placebo group, n=12 in the minocycline group), and dermatological (n=10 in the placebo group, n=8 in the minocycline group). Interpretation: Minocycline does not benefit negative or other symptoms of schizophrenia over and above adherence to routine clinical care in first-episode psychosis. There was no evidence of a persistent progressive neuropathic or inflammatory process underpinning negative symptoms. Further trials of minocycline in early psychosis are not warranted until there is clear evidence of an inflammatory process, such as microgliosis, against which minocycline has known efficacy. Funding: National Institute for Health Research Efficacy and Mechanism Evaluation (EME) programme, an MRC and NIHR partnership.